Fungsi Dan Makna Point Of Interest Dalam Unsur Grafis Pada Label Makanan Tradisional Getuk Goreng Di Sokaraja - Nawang Nila; Ana Rosmiati (ISI Press Institut Seni Indonesia Surakarta, 2021)
Point of Interest (center of attention) becomes important for identity on product labels for Sokaraja fried getuk packaging. On each label, Sokaraja fried getuk uses a different center of attention from one label to another. This study aims to determine the role of the center of interest in the fried getuk label. The research method used is descriptive qualitative research by extracting data from primary and secondary sources such as interviews and literature studies. Through the perspective of the theory of graphic elements and design principles as the unit of analysis for the label of getuk goreng Sukaraja. Based on data analysis, it was concluded that the Sokaraja Fried Getuk Label has the characteristics of traditional visual elements and is dominated by red. Aspects of typography tend to be serif, sans serif, and script, using symmetrical and asymmetrical compositions. Design principles such as unity, proportion, balance, rhythm, and emphasis are visual elements that are composed quite well.